Governance in the business environment - Aras, Guler; Crowther, David (Bingley, U.K. : Emerald, 2011)
Governance is very much a current concern in the public interest. The global economic recession, from which we are just emerging, has highlighted failures in governance and regulation with much blame being laid at the feet of regulators and demands for perpetrators to be sanctioned accordingly. A key to managing the prevention of future financial crisis is concerned with the recognition and regulation of a truly global market for finance, trade, labour etc. and accepting that there are different perspectives from different parts of the world. Published in association with the Social Responsibility Research Network, Volume 2 in this new and exciting series recognises these issues and takes a global interdisciplinary perspective to the matter of governance in the business environment. Contributions range from the UK, Portugal and Belgium to Brazil, Japan, China and Malaysia, and topics of investigation include: governance and the management of global markets; governance mechanisms of strategic alliances in the Japanese car industry; multinational corporations and democratic governance; market governance to governance in the market - a return to old order; and a socio-legal framework for governance.
Introduction / G$1#7H(Ber Aras, David Crowther -- ch. 1. Governance and the management of global markets / G$1#7H(Ber Aras, David Crowther -- ch. 2. Developing a socially responsible information technology environment / David Crowther, Ana Maria Davila Gomez -- ch. 3. Corporate social responsibility and marketing / Georgiana F. Grigore -- ch. 4. Multinational corporations, governments and corporate governance / Kamil Omoteso -- ch. 5. The utilitarian fallacy / David Crowther -- ch. 6. Strategic alliances in the Japanese car industry / Nabyla Daidj -- ch. 7. Development of corporate social responsibility in China / Lan Jiang -- ch. 8. CSR in the context of globalisation in Mauritius / Roshni Deepa Gokulsing -- ch. 9. The extent of disclosure of corporate social responsibility in Malaysia / Roshima Said, Hilwani Hariri, Hasnah Haron, Yuserrie Hj. Zainuddin -- ch. 10. Corporate social responsibility and sustainability / Elizabeth de Melo Rico.s
Includes index.
Keywords: Business ethics